The Role of Multistakeholder Platforms in Environmental Governance: Analyzing Stakeholder Perceptions in Kalomo District, Zambia, Using Q-Method - Siangulube, F.S. (Springer, 2024)
Multistakeholder platforms (MSPs) are increasingly applied in environmental governance as institutions to collectively negotiate challenges, opportunities, and policy options in contested landscapes. However, their contributions and effectiveness depend on how stakeholders perceive and frame the role of MSPs in addressing social and environmental challenges. Despite this dependence, stakeholder perceptions of MSPs are currently under-researched. Hence this empirical study carried out in Zambia’s Kalomo District asks: how do stakeholder groups perceive the role of MSPs in addressing landscape challenges, given the context of the dual land tenure system, and what does this imply for the implementation of integrated landscape approaches? This study uses Q-methodology to analyze the perceptions of purposefully selected stakeholders from state institutions, civil society organizations, land users, and others familiar with existing MSPs at the district and village levels. The findings reveal three narratives. The first one presents MSPs as institutions that foster dialogue. The second narrative foregrounds the role of the government and private sector, despite acknowledging the diversity of stakeholders in MSPs. In this narrative, MSPs should focus on supporting market-driven solutions to resolve landscape challenges. The third narrative recognizes power imbalances and considers MSPs as institutions to identify policy gaps and needs. The first two narratives are positioned in Dryzek’s discourse classification as environmental problem-solving, while the third inclines toward green radicalism. Despite this divergence, there was consensus that MSPs have the potential to harmonize policies in a dual governance system and encourage dialogue between stakeholders to reconcile landscape challenges.